Overview of Islamic Boarding School Educational Communication Media: A Bibliometric Analysis Study - Darmawati Darmawati (Madania: Jurnal Ilmu-Ilmu Keislaman, 2022)
This study assesses the most relevant themes related to Islamic Boarding School Education Media with bibliometric analysis using the keywords "educational media "OR" boarding school education "OR" boarding school technology "OR" education communication"   as input to gain a full understanding of Islamic Boarding School Education Media and understand the current research concentration. Using the Scopus data source as it is considered the best choice for bibliometric analysis. The method used is literature review using bibliometric analysis to visualize the network of authors, citations and keywords, VOSviewer software. The results show that Every year, there are more and more papers on Islamic Boarding School Education Media, a trend that shows an increasing interest in the subject. Wong, K.M is a writer who has the most citations and documents overall while United State is the country that has published the most articles. Bibliometric analysis offers relevant details regarding the main issues studied about Islamic Boarding School Education Media.